How Transformational Leadership Enhancing School's Performance: a Systematic Literature Review - Sianipar, Ardin; Putri, Ayu Yulianti (International Journal of Social and Management Studies, 2024)
Abstract - This study aims to systematically review the literature on how transformational leadership can improve school performance, as well as identify the factors that play a role in the effectiveness of such leadership in the educational environment. Using a systematic literature review (SLR) of empirical articles from leading journals in the past five years, the study filtered and encoded key findings to understand the influence of transformational leadership. The findings show that transformational leadership significantly improves school performance through teacher motivation, collaborative culture development, and increased staff commitment. Trust, collegial support, and the school climate often mediate these effects. The main limitation of this study is that the scope of the data is limited by periods and geographical regions, which may affect the generalization of the findings. Further research is recommended to explore the long-term impact and integrate cross-cultural perspectives. These results guide school leaders and policymakers in developing effective leadership strategies to improve performance.